2013
DOI: 10.1007/s11682-013-9228-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated prefrontal myo-inositol and choline following breast cancer chemotherapy

Abstract: Breast cancer survivors are at increased risk for cognitive dysfunction, which reduces quality of life. Neuroimaging studies provide critical insights regarding the mechanisms underlying these cognitive deficits as well as potential biologic targets for interventions. We measured several metabolite concentrations using 1H magnetic resonance spectroscopy as well as cognitive performance in 19 female breast cancer survivors and 17 age-matched female controls. Women with breast cancer were all treated with chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 62 publications
0
24
0
5
Order By: Relevance
“…1C) mirror the pattern of their alterations in colorectal cancer, where glucose and myo-inositol are decreased while lactate and taurine are increased compared to normal tissues (34). Specifically to myo-inositol, it has been also reported that this metabolite was significantly increased in breast cancer survivors who underwent chemotherapy (44) and in healthy control subjects compared to men with prostate cancer (45). These findings suggest that the drop in myo-inositol levels is a common trend in malignancies.…”
Section: Discussionmentioning
confidence: 94%
“…1C) mirror the pattern of their alterations in colorectal cancer, where glucose and myo-inositol are decreased while lactate and taurine are increased compared to normal tissues (34). Specifically to myo-inositol, it has been also reported that this metabolite was significantly increased in breast cancer survivors who underwent chemotherapy (44) and in healthy control subjects compared to men with prostate cancer (45). These findings suggest that the drop in myo-inositol levels is a common trend in malignancies.…”
Section: Discussionmentioning
confidence: 94%
“…Findings from fMRI studies are supported by results from complementary techniques, including positron emission tomography, arterial spin labeling, and electroencephalography (EEG) . Magnetic resonance spectroscopy imaging has also provided further insight regarding certain pathophysiologic mechanisms, including inflammation and demyelination …”
Section: Chemotherapy Endocrine Therapy and Cognitionmentioning
confidence: 93%
“…BCC survivors show elevated neurochemical markers of microglial activity (i.e. myo-inositol) (Kesler, et al, 2013b) and increased peripheral pro-inflammatory cytokines levels (Ganz, et al, 2013;Kesler, et al, 2013a;Kesler, et al, 2013b;Pomykala, et al, 2013b;Vardy, et al,2007). Compared to healthy women, BCC survivors show increased pro-inflammatory cytokine levels with increased age (Kesler, et al, 2013a).…”
Section: Brain Aging Cancer and Chemotherapymentioning
confidence: 99%